Comparison of Islamic Commercial Banks and Islamic Business Units: Which Is More Efficient? - Kurniawan, Zulfa Ahmad Kurniawan (Islamic Economics Journal, 2025)
Although Islamic banks have been present in Indonesia for three decades, their market share remains significantly behind that of conventional banks. In response, regulators have mandated that Islamic Business Units (UUS) be converted into full-fledged Islamic Commercial Banks (BUS) once specific criteria are met. This study aims to analyze the development of operational efficiency between BUS and UUS in Indonesia. The research uses secondary data from the 2015-2024 period obtained from OJK Islamic banking statistics. The methods employed include descriptive statistical analysis and the nonparametric Mann-Whitney U test. The findings reveal a statistically significant difference in efficiency between BUS and UUS, as reflected by the BOPO ratio, with UUS proving to be more efficient than BUS. Theoretically, this study provides new and updated insights into the cost efficiency management capabilities of BUS and UUS. These findings also highlight the need for policymakers to ensure that the separation does not compromise efficiency while maintaining the sustainability of Islamic banks.